(untitled) (Bangladesh Journal of Urology, 2023)
Background: Stricture of the female urethra is considered to be a less common disease accounting for 4%–13% of women who present with bladder outlet obstruction. Almost all strictures can have idiopathic, iatrogenic, inflammatory, or traumatic etiologies. The most common symptoms are dysuria, urgency, frequency, and poor flow. FUS can also lead to overt urine retention and recurrent UTIs. We present our experiences in single-stage labial mucosal substitution urethroplasty technique for urethral stricture. The objectives were to evaluate the clinical outcome, symptom improvement, success rate and complications of the performed procedure. Methods: This quasi-experimental study was conducted from January 2016 to December 2021, at the department of Urology, BIRDEM General Hospital, Enam Medical College Hospital, Dhaka Community Medical College Hospital, Evercare Hospital and a Private Clinic in Uttara, Dhaka. The study was conducted on 60 females with urethral stricture who underwent labial mucosal graft urethroplasty. Follow up period for all the respondents was 1 year. Statistical analysis was performed using SPSS version 21. Results: 60 patients of urethral stricture underwent labial mucosal graft urethroplasty. The average follow-up time was 12 months, with a mean age of the patients was 41 years. 31 patients (51.67%) had idiopathic urethral stricture, 20(33.33) had iatrogenic disease, 4(6.67%) had traumatic urethral stricture and 5 (8.33%) had history of recurrent (nonspecific) urethritis. The mean±SD of operative time was 90±11.12 min and the success rate was 100%. No patient mentioned having any severe postoperative pain or unpleasant urethral discharge (wound infection). All of the patients had good voiding 1-year follow-up and there was no report of vaginal narrowing or dyspareunia. During routine follow-up, stricture recurrence was found in only two individuals, after 24 months, which were managed by urethral calibration. Conclusion: Labial mucosal substitution urethroplasty is an effective and sustainable reconstructive technique for female urethral stricture with very low rate of recurrence. It is an uncomplicated surgical method with good reproducibility. Bangladesh J. Urol. 2023; 26(2): 78-83